Evaluasi kinerja petugas vaksin rabies di Kota Ambon - Astri Dwyanti Tagueha; Heru Susetya; Setyawan Budiharta (Jurnal Sain Veteriner, 2011)
Study on the evaluation of rabies vaccinator performance and its associated factors on has been conduced.